Identification of second instar larvae of thrips (Thysanoptera: Thripidae) vectors of Orthotospovirus (Tospoviridae) in South America - Lima, Élison F.B.; Silva, Larinne de M.R.; Fontes, Lúcia da S.; De Borbon, Carlos Manuel (Wiley, 2022)
Thrips (Thysanoptera: Thripidae) are the only vectors of Orthotospovirus, a group of viral pathogens that infect plants and cause major economic damage to crops. The virus is acquired by the vector only at the first and early second larval stages and transmitted to plants by adult thrips through the circulatory system and via propagation. Since these vector immatures play a key role in the virus cycle, larval identification can be important for decision-making about the management of each virus and vector. Thrips identification is mostly based on adult morphology, but second instar larvae recognition can be reliable and may provide advanced diagnosis about the presence and identity of the vector even in the absence of adults. Here, we present an identification tool for second instar larvae of the seven thrips species known to be Orthotospovirus vectors in South America – Frankliniella gemina, F. occidentalis, F. schultzei, F. zucchini, Scirtothrips dorsalis, Thrips palmi and T. tabaci. An illustrated key along with descriptions and comments on each of these species in the continent is provided.